A case of primary rectal teratoma - Aiken, Aikepaer; Yu, Wen; Abudoureyimu, Aini; Aizimu, Xuelaiti; Tong, Jinlu (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Aiken A. Yu W, Abudoureyimu A. Aizimu X. Tong J. A case of primary rectal teratoma. Turk J Gastroenterol 2020; 31(11): 835-7.